Slums: perspectives on the definition, the appraisal and the management of an urban phenomenon - Nuissl, Henning; Heinrichs, Dirk (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
The contribution provides a basic introduction to the topic. It outlines the term ‘slum’, details the challenges associated with this form of settlement in the literature and the public opinion, and profiles the development approaches and solutions to overcome the problems associated with the slum phenomenon. The principal aim of the article is to illustrate that there are different approaches to define, assess and solve the problems of informal settlements and their inhabitants. The paper emphasises the complexity and variety of slums worldwide as well as the controversial perspectives adopted towards them. It shows how the normative framing of different actors associated with the ‘slums of hope’ and the ‘slums of despair’ and shaped strategies and action to resolve and overcome the material, social and institutional challenges of the slums.